The Effect of Quality Financial Reporting on Good Governance - Safkaur, Otniel; Afiah, Nunuy Nur; Poulus, Sugiono; Dahlan, Muhammad (International Journal of Economics and Financial Issues, 2019)
One of the factors triggering a lack of financial reporting caused by dishonest application of records, it has not been effectively transparent and accountable by various government agencies in Indonesia. This study aims to find out how the application of the accrual basis in accounting records in the government and its effect on good governance. This study uses a method of verifying causality to determine the influence between variables. The population in this study were 44 regency and city governments in the provinces of Papua and West Papua. Whereas the Observation Unit is DPPKAD in 44 Provinces/Cities/Districts in the regions of Papua and West Papua. The sampling technique uses a census so that all members of the population become the study sample. The results of this study show empirical evidence that the application of the accrual basis of financial reporting affects good governance resulting from financial reporting of 44 district and city governments in the provinces of Papua and West Papua. Keywords: Financial reporting, Organizational structure, Good governance JEL Classifications: G2, G3 DOI: https://doi.org/10.32479/ijefi.8047